History of Algerian and Maghreb immigration to France - Chaouche , Hamid (The Algerian Historical Journal, 2026)
This study aims to reconstruct the history of Algerian and Maghreb immigration in France from its beginning till the end of the 20th century. In order to do this, we reviewed the most important stages of this immigration and some of its sociological and demographic characteristics. Then, we also provided in this article some figures relating to the number of immigrants generated and generating this process through its different ages. Finally, we addressed the most important factors that caused maintained then transformed this immigration as it developed.